2018
DOI: 10.1038/s41366-018-0120-3
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of habitual physical activity in over 377,000 UK Biobank participants identifies multiple variants including CADM2 and APOE

Abstract: Background/ObjectivesPhysical activity (PA) protects against a wide range of diseases. Habitual PA appears to be heritable, motivating the search for specific genetic variants that may inform efforts to promote PA and target the best type of PA for each individual.Subjects/MethodsWe used data from the UK Biobank to perform the largest genome-wide association study of PA to date, using three measures based on self-report (nmax=377,234) and two measures based on wrist-worn accelerometry data (nmax=91,084). We ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
371
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 300 publications
(384 citation statements)
references
References 83 publications
(75 reference statements)
12
371
1
Order By: Relevance
“…We previously observed 5 using MR that while objective measures of physical activity (not included here) are linked to reduced odds of depression, selfreport measures of physical activity do not necessarily show these patterns. Objective measures of physical activity-reflecting a broad tendency for movement/activity-have demonstrated higher heritability 33 and may yield more powerful genetic instruments in an MR framework.…”
Section: Discussionmentioning
confidence: 99%
“…We previously observed 5 using MR that while objective measures of physical activity (not included here) are linked to reduced odds of depression, selfreport measures of physical activity do not necessarily show these patterns. Objective measures of physical activity-reflecting a broad tendency for movement/activity-have demonstrated higher heritability 33 and may yield more powerful genetic instruments in an MR framework.…”
Section: Discussionmentioning
confidence: 99%
“…Summary-level data were obtained from a recently published GWAS on accelerometer-measured physical activity conducted within UK Biobank 10 . In this GWAS, the regression models were adjusted for age, sex, the first ten genomic principal components, center, season (month), and genotyping chip.…”
Section: Data On Physical Activitymentioning
confidence: 99%
“…We used a two-sample MR framework to examine potential causal associations between objective accelerometer-measured physical activity and risks of breast and colorectal cancer using genetic variants associated with accelerometer-measured physical activity identified from a recent genome-wide association study (GWAS) 10 . We examined the associations of these genetic variants with risks of breast cancer 11 and colorectal cancer 12 .…”
Section: Introductionmentioning
confidence: 99%
“…For exercise, twin studies investigating leisure‐time physical activity (LTPA), physical activity (PA), physical inactivity (PI) and sedentary behaviors have yielded heritability estimates ranging from ~25 to 85% in humans . In addition, recent genome‐wide association studies of exercise behaviors identified a few genes reaching significance . These include genes highly expressed in the mesolimbic system of the brain, including DRD2 , SLC9A9 and GABRG3 .…”
Section: Role Of Genetics In Auds and Exercisementioning
confidence: 99%
“…[95][96][97][98] In addition, recent genome-wide association studies of exercise behaviors identified a few genes reaching significance. 99,100 These include genes highly expressed in the mesolimbic system of the brain, including DRD2, SLC9A9 and GABRG3. 99,100 DRD2 codes for the dopamine D2 receptor and was identified as significant in genome-wide association studies of both alcohol and exercise behaviors.…”
Section: Role Of Genetics In Auds and Exercisementioning
confidence: 99%